Comparative analysis of the structural and physical properties of magnetron Co-sputtered Ag-doped and Si-doped hydroxyapatite coatings on titanium substrates. Issue 180 (4th May 2017) - Agyapong, Dorothy Araba Yakoba; Zeng, Hongjuan; Du, Wenju; Acquah, Isaac; Liu, Yiyao
ABSTRACT: This study compares the structural and physical properties of Si-doped hydroxyapatite coatings deposited by magnetron sputtering on mechanically polished titanium substrates to Ag-HA using the combined techniques of XRD, RHEED and SEM, as a function of increasing Si and Ag contents and annealing temperature. The results obtained revealed that the annealing temperature as well as silver and silicon contents of both surface coatings determine the crystal structure of the coated sample surface. Silver proved to affect the crystallization of HA as the RHEED patterns in the 30 W Ag coating showed clouded rings. In the Si-HA coating, increased silicon content inhibited HA crystallization, but as the annealing temperature was increased, titanium ions penetrated the HA coatings forming rutile on the surface of the material and again the effect of silicon preventing rutile crystallization process instead of HA was experienced.